Effect of inter-pregnancy interval on maternal and fetal outcome - Shrestha, Pravin; Mahato, Vibha; Karmacharya, Smita (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To explore the impact of inter-pregnancy interval on maternal and fetal health Methods: Descriptive cross sectional study conducted at Department of Obstetrics and Gynaecology, Manipal Teaching hospital, Pokhara, Nepal. Inter-pregnancy interval (IPI) was calculated as the time elapsed between the woman’s last delivery and the date of last menstrual period for the present second or higher order birth. Intervals were taken in weeks and then converted to months. IPI were categorized as <18months, 18-23, 24-59, >59 months. Results: Among the 550 pregnancies studied, the majority (57%) of them had an IPI of more than 59 months. Long IPI of >59 months had increased risk of maternal complications like preeclampsia (12.4%), postdate pregnancy (10.8%), PROM (4.4%), oligohydramnios (3.8%), placenta previa (2.5%), gestational diabetes mellitus (2.2%), chronic hypertension (1.5%), abruptio placenta (0.3%), IUFD (0.6%) and overt DM (0.3%). Increased preterm birth was seen in IPI <18 months (25%). Short IPI had also increased risk of IUGR (8.3%) and anaemia. Adverse maternal outcome was least when IPI was between 18-23 months. Conclusions: IPI shorter than 18 months and longer than 59 months were associated with increased risk of adverse maternal and perinatal outcomes. Keywords: fetal, inter-pregnancy, interval